2021
DOI: 10.3390/ijerph182111489
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Occupational Health Hazards among Health Care Workers of Northern Saudi Arabia: A Multicenter Study

Abstract: Health care workers (HCWs) working in different health care facilities are exposed to many hazards, especially during the COVID-19 pandemic. This questionnaire-based cross-sectional study aimed to assess the prevalence, pattern, and risk factors of occupational health hazards faced by 438 randomly selected HCWs from northern Saudi Arabia. The HCWs are commonly exposed to needle stick injuries (34.5%) under the biological hazards category; and work-related stress (69.6%) under the non-biological hazards categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…A recent study from Saudi Arabia revealed that nearly two-thirds (68.5%) of the study population were exposed to one or more biological health hazards including needle stick injuries. These biological health hazards were significantly higher among the HCWs working in higher centers, tertiary, or specialty hospitals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Saudi Arabia revealed that nearly two-thirds (68.5%) of the study population were exposed to one or more biological health hazards including needle stick injuries. These biological health hazards were significantly higher among the HCWs working in higher centers, tertiary, or specialty hospitals [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, both work together to build a better future-a more sustainable world [3,7,[10][11][12][13][14][15][16]. OSH is generally defined as the science of the anticipation, recognition, evaluation, and control of hazards arising in or from the workplace that could impair the health and well-being of workers, taking into account the possible impact on the surrounding communities and the general environment [17,18]. A multidisciplinary activity focuses on fostering a safe and healthy working environment [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although OSH appears to be a social matter, work-related accidents were responsible for the deaths of 1.9 million people in 2016, according to the World Health Organization (WHO) and ILO [25,26]; its economic dimension is not to be underestimated. Work-related mortality accounted for 5% of all deaths worldwide [18,27]; a toll that has increased dramatically due to the COVID-19 pandemic [28][29][30]. Early efforts to quantify the economic impact of work-related accidents and diseases suggest two distinct cost categories: human and economic.…”
Section: Introductionmentioning
confidence: 99%
“…India has a healthcare work force of over 5 million[ 1 ] catering to the needs of over 1.3 billion people. [ 2 ] These healthcare providers are prone to occupational hazards[ 3 ] including biological, physical, chemical, radiological, ergonomic, and psycho-social hazards. Approximately 52% hepatitis C virus (HCV), 42% hepatitis B virus (HBV), and 8% human immunodeficiency virus (HIV) in healthcare workers is attributable to contaminated sharps.…”
Section: Introductionmentioning
confidence: 99%